2002
DOI: 10.1074/jbc.m201227200
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolar Localization Domain of the Catalytic Subunit of Human Telomerase

Abstract: Telomerase is the enzyme essential to complete the replication of the terminal DNA of most eukaryotic chromosomes. In humans, this enzyme is composed of the telomerase reverse transcriptase (hTERT) and telomerase RNA (hTR) subunits. hTR has been found in the nucleolus, a site of assembly of ribosomes as well as other ribonucleoproteins (RNPs). We therefore tested whether the hTERT component is also found in the nucleolus, where it could complex with the hTR RNA to form a functional enzyme. We report here that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 46 publications
6
85
1
1
Order By: Relevance
“…The DAT mutants were previously reported to retain the capacity to promote the non-canonical functions of TERT in chromatin remodeling and are therefore competent to promote DNA-damage repair, despite defects in their canonical TERT functions . We also included three telomerase-RNA-binding-defective TERT mutants (FYAA561, RBD386 and RBD512; Etheridge et al, 2002). Although our earlier experiments demonstrated that the expression of both TERT and TER components were necessary to support telomerase growth-promoting functions in ALT cells, we could not rule out the possibility that these two telomerase components were working independently.…”
Section: Resultsmentioning
confidence: 99%
“…The DAT mutants were previously reported to retain the capacity to promote the non-canonical functions of TERT in chromatin remodeling and are therefore competent to promote DNA-damage repair, despite defects in their canonical TERT functions . We also included three telomerase-RNA-binding-defective TERT mutants (FYAA561, RBD386 and RBD512; Etheridge et al, 2002). Although our earlier experiments demonstrated that the expression of both TERT and TER components were necessary to support telomerase growth-promoting functions in ALT cells, we could not rule out the possibility that these two telomerase components were working independently.…”
Section: Resultsmentioning
confidence: 99%
“…It is yet to be determined whether hTERT binds to any specific sequence of total genomic DNA. However, Etheridge et al (2002) have demonstrated that hTERT localizes to the nucleolus. In contrast to this, hTERT binding to telomeres is dependent on hTR as well as the RT motif, which suggests that hTERT must be functionally reconstituted in order to interact with telomeres so that it could provide the function of replenishing the telomeric DNA.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that hTERT interactions with telomeres may influence the association between telomeres and nuclear matrix. Recently, we and others have shown that hTERT is present throughout the nucleus but in certain instances hTERT is concentrated in the nucleolar organizing region (Tahara et al, 1999;Vaziri et al, 1999;Kawakaim et al, 2000;Wood et al, 2001;Etheridge et al, 2002). More directly, telomeres have been shown cytologically as well as biochemically to be tethered to the nuclear matrix (Smith and de Lange, 1997;Pandita, 2002).…”
Section: Htert Expression Influences Telomere-nuclear Matrix Associationmentioning
confidence: 99%
“…Notably, a recent report identified a nucleolar localization signal in TERT 9 . Interestingly, the nucleolar localization of TERT appears to be unrelated to its telomerase function 10 .…”
mentioning
confidence: 99%